Direct Health Care Costs Associated with Asthma in British Columbia - Mohsen Sadatsafavi; Larry Lynd; Carlo Marra; Bruce Carleton; Wan C Tan; Sean Sullivan; J Mark FitzGerald (Canadian Respiratory Journal)
BACKGROUND: A better understanding of health care costs associated with asthma would enable the estimation of the economic burden of this increasingly common disease.